2001
DOI: 10.1101/gad.864201
|View full text |Cite
|
Sign up to set email alerts
|

E2Fs regulate the expression of genes involved in differentiation, development, proliferation, and apoptosis

Abstract: The retinoblastoma protein (pRB) and its two relatives, p107 and p130, regulate development and cell proliferation in part by inhibiting the activity of E2F-regulated promoters. We have used high-density oligonucleotide arrays to identify genes in which expression changed in response to activation of E2F1, E2F2, and E2F3. We show that the E2Fs control the expression of several genes that are involved in cell proliferation. We also show that the E2Fs regulate a number of genes involved in apoptosis, differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
580
3
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(618 citation statements)
references
References 60 publications
24
580
3
6
Order By: Relevance
“…Several different approaches have been carried out. Initial microarray screens focused on the overexpression of E2F or Rb family members (Muller et al, 2001;Polager et al, 2002). While these studies identified large arrays of altered genes, they cannot distinguish genes directly regulated by Rb or E2F from genes that changed expression due to secondary effects of Rb or E2F expression (such as alterations in the cell cycle).…”
Section: Transcriptional Targets Of Rb and E2f Proteinsmentioning
confidence: 99%
“…Several different approaches have been carried out. Initial microarray screens focused on the overexpression of E2F or Rb family members (Muller et al, 2001;Polager et al, 2002). While these studies identified large arrays of altered genes, they cannot distinguish genes directly regulated by Rb or E2F from genes that changed expression due to secondary effects of Rb or E2F expression (such as alterations in the cell cycle).…”
Section: Transcriptional Targets Of Rb and E2f Proteinsmentioning
confidence: 99%
“…Overexpression of E2F drives cell proliferation, and thus the induction of reporter activity shown above had the possibility of secondary transcriptional change caused by an accelerated cell cycle (Muller et al, 2001). In order to verify whether RB/E2F directly regulates the ECT2 promoter, we used a chromatin immunoprecipitation (ChIP) assay.…”
Section: Rb Disruption Induces Aberrant Ect2 Expression T Eguchi Et Almentioning
confidence: 99%
“…However, E2F1À/À knockout mice develop a broad spectrum of tumors, suggesting that E2F1 also functions as a tumor suppressor. Indeed, several authors reported that E2F1 can induce apoptosis through p53-dependent (Kowalik et al, 1995;Qin et al, 1994;Wu and Levine, 1994) and p53-independent mechanisms (Irwin et al, 2000), by upregulating apoptotic genes like Apaf-1 (Furukawa et al, 2002), p73 (Stiewe and Putzer, 2000), caspase 3 and 7 (Muller et al, 2001), Noxa and PUMA (Hershko and Ginsberg, 2004). Furthermore, forced expression of E2F1 caused increased sensitivity to DNA-damaging agents and topoisomerase II inhibition in a p53-independent manner (Nip et al, 1997).…”
Section: Introductionmentioning
confidence: 99%